Fixed income modelling - Munk, Claus (Oxford : Oxford University Press, 2011)
A large number of securities related to various interest rates are traded in financial markets. Traders and analysts in the financial industry apply models based on economics, mathematics and probability theory to compute reasonable prices and risk measures for these securities. This book offers a unified presentation of such models and securities.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Fixed-income securities -- Econometric models